Molecular Basis of Ubiquitination Catalyzed by the Bacterial Transglutaminase MavC. Issue 12 (30th April 2020) - Guan, Hongxin; Fu, Jiaqi; Yu, Ting; Wang, Zhao‐Xi; Gan, Ninghai; Huang, Yini; Perčulija, Vanja; Li, Yu; Luo, Zhao‐Qing; Ouyang, Songying
Abstract: The Legionella pneumophila effector MavC is a transglutaminase that carries out atypical ubiquitination of the host ubiquitin (Ub)‐conjugation enzyme UBE2N by catalyzing the formation of an isopeptide bond between Gln40Ub and Lys92UBE2N, which leads to inhibition of signaling in the NF‐κB pathway. In the absence of UBE2N, MavC deamidates Ub at Gln40 or catalyzes self‐ubiquitination. However, the mechanisms underlying these enzymatic activities of MavC are poorly understood at the molecular level. This study reports the structure of the MavC–UBE2N–Ub ternary complex representing a snapshot of MavC‐catalyzed crosslinking of UBE2N and Ub, which reveals the way by which UBE2N–Ub binds to the Insertion and Tail domains of MavC. Based on the structural and experimental data, the catalytic mechanism for the deamidase and transglutaminase activities of MavC is proposed. Finally, by comparing the structures of MavC and MvcA, the homologous protein that reverses MavC‐induced UBE2N ubiquitination, several essential regions and two key residues (Trp255MavC and Phe268MvcA ) responsible for their respective enzymatic activities are identified. The results provide insights into the mechanisms for substrate recognition and ubiquitination mediated by MavC as well as explanations for the opposite activity of MavC and MvcA in terms of regulation of UBE2N ubiquitination. Abstract : The pathogen Legionella pneumophila evades immune detection by deploying the transglutaminase effector MavC to ubiquitinate the host ubiquitin‐conjugating enzyme UBE2N. This work presents the structure of MavC–UBE2N–Ub ternary complex and sheds light on the molecular basis for MavC‐induced transglutamination and its mechanistic differences with its homolog MvcA, which counteracts MavC activity by deubiquitinating modified UBE2N in later phases of infection.